CHINA IN AFRICA: A THREAT TO AFRICAN COUNTRIES? (The Strategic Review for Southern Africa, 2020)
China's growing presence in Africa has led to a debate about whether China is becoming a threat to African countries or not. While some argue that China is not posing any threat to Africa, others believe that China is not only a threat but also becoming a new coloniser. By exploring the existing literature, and the relevant information about China in Africa, this article demonstrates that there is an emerging contradiction in China's growing presence in Africa. This contradiction is manifest by the Chinese state's official policy toward Africa and the Chinese nonstate actors' behaviour on the ground. While the former has long-term comprehensive interests in Africa, and therefore works toward building an equal and win-win Sino-African partnership, the latter, who in many cases are actually agents for the former to realise that partnership, have short-term 'for-profit interests' in Africa and therefore behave like an exploiter. This is one of the reasons why there are conflicting findings about China in Africa: while observers focusing on the Chinese government's official policy toward Africa tend to find that China is no threat to Africa, those who pay attention to the words and deeds of the Chinese non-state actors in Africa would find the opposite. The discussion of this contradiction is not only academically worthwhile but also practically important. In order to develop and maintain the 'constructive relations' with Africa, this contradiction in China's growing presence in Africa is arguably one of the largest challenges that the Chinese government has to deal with today.